“Investigate Edge Distortion Within Captured Image Under Low Lighting” - Jabbar Karam, Ali; Abid D.Al – Zuky2, Ali; H.Mahdy, Anwar; J. Mohamad, Haidar (مجلة كلية التربية, 2020)
Study and analysis image processing that deals with low lightness and low contrast has major importance in many applications and fields. Images captured in low-light environment companied always with noise and distortion. This considered a big problem in digital image processing. So, a focused study in this paper achieving at low lightness condition effect for captured images using two types of camera (Samsung and Sony). Lighting is controlled by self-proposed lighting system. This system has three florescent lights with different size and power to control light environment. Test image (black and white) used to study distortions that formed at edges image as a result of low lightness due to noise. This study focused on edge contrast, number of edge points and comparison between edge points for the best image picture lighting (80) Lux and group image under low lightness (1) Lux to see number of edges that added or removed as a function of light intensity. It shown that Sony is better than Samsung camera depending on edge contrast and common edge points under low lightness condition. These methods are good indicators to estimate the quality of images and cameras.